(3TQM cahj ef GdBOGHs - (3GdbQg MUGQj GdQhej, GdMfaj, YeQ Hf MSjf (B, (3J (B1200 (3g`s ((3eOQSI ejQejQGfs)
(3ChdgG (B:s
(3UGQaG dYfGf GdKfGA Edi hdjg GdPj COHfG HGdefGXQI (B... (3dheG cGfJ GdQSGdI GdcahjI aj GdBOGH UGQYI aj ejOGf GdGPcjGA hChdj GdCdHGH heTJedI Ydi ahGFO aQGFO JWdbJ HgG cJH GdCbOejf (B...s
(3BNQgG (B:s
...(3aGfXQ aj GdHMK GdKGfj CjVG Ydi GdhLg GdSGHb be aj GdKGdK Ke aj GdQGHY gcPG MJi JQJbj Edi eOGQL JejjR GdebHhd ef GdeQOhO hJchf ef GdebHhd hdG Jchf ef GdeQOhO heG Jajbj EdG HGddg (B... (3JeJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B2\558s
(3EjVGM Gdecfhf (B1\3s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdadSaI hGdefWbs